2019
DOI: 10.1186/s12879-019-4725-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microglia/macrophages in the granuloma microenvironment of encephalic schistosomiasis japonicum

Abstract: BackgroundEgg-induced immune response and granuloma formation are thought to be the basis of central nervous system (CNS)-related clinical symptoms of Schistosoma japonicum. Microglia/macrophages are the major immune cells involved in detection and subsequent elimination of pathogens and injured tissue in the brain. However, little is known about their role in the pathogenesis of neuroschistosomiasis. The main purpose of the study is to clarify the pathological involvement of microglia/macrophages in the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…IL-6 and IL-10 are important proinflammatory cytokines and antiinflammatory cytokines, respectively (Kumar et al, 2021). Higher numbers of macrophages were found in the livers of infected WT and TLR7 KO mice, which expressed higher levels of CD86 and secreted more IL-4, IL-10, and IL-12, suggesting that macrophages played an important role in the progression of S. japonicum infection-induced hepatitis, as previously reported (Tan et al, 2019;Ye et al, 2020). Although the number of macrophages in the livers of infected TLR7 KO mice was similar to that in infected WT mice, they expressed lower CD86 levels and produced fewer cytokines.…”
Section: Discussionsupporting
confidence: 69%
“…IL-6 and IL-10 are important proinflammatory cytokines and antiinflammatory cytokines, respectively (Kumar et al, 2021). Higher numbers of macrophages were found in the livers of infected WT and TLR7 KO mice, which expressed higher levels of CD86 and secreted more IL-4, IL-10, and IL-12, suggesting that macrophages played an important role in the progression of S. japonicum infection-induced hepatitis, as previously reported (Tan et al, 2019;Ye et al, 2020). Although the number of macrophages in the livers of infected TLR7 KO mice was similar to that in infected WT mice, they expressed lower CD86 levels and produced fewer cytokines.…”
Section: Discussionsupporting
confidence: 69%
“…Schistosoma japonicum (S. japonicum), prevalent in Southeast Asia, mainly affects the brain (encephalic schistosomiasis japonicum) (223,224). A recent study has shown that CNS macrophages including microglia play a role in forming granulomas that isolate and neutralize the infecting parasite eggs (225). Interestingly, another study utilizing mice with S. japonicum ova-induced granulomas has shown alterations in the intestinal barrier and the gut microbiota composition upon infection (226).…”
Section: Microbial and Parasitic Infectionsmentioning
confidence: 99%
“…Schistosoma eggs secrete antigens such as glycans and glycoproteins that elicit an immune response leading to granuloma formation ( 230 , 233 , 236 ). In both human cases with neuroschistosomiasis caused by S. japonicum and mice that were injected with S. japonicum eggs in the brain microglia/macrophages constituted the major components of the granulomas surrounding the eggs ( 237 ). Patients with spinal cord schistosomiasis have increased levels of IL-1beta, IL-4, IL-6 and IL-10 and low concentrations of TNF-α and IFN-γ in both CSF and serum ( 238 ).…”
Section: Other Parasitesmentioning
confidence: 99%